2019
DOI: 10.1002/mp.13603
|View full text |Cite
|
Sign up to set email alerts
|

A depth encoding PET detector using four‐crystals‐to‐one‐SiPM coupling and light‐sharing window method

Abstract: Purpose Depth of interaction (DOI) decoding capability is of great importance for positron emission tomography (PET) requiring high resolution. In this study, we presented a novel low‐cost DOI detector design with four crystals coupling to one SiPM, based on the method of rectangular light‐sharing window (RLSW). A prototype detector was constructed, calibrated, and assessed using the methods of homogeneous radiation and flood map analysis. Methods The DOI detector was constructed with a 4 × 4 array of lutetium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The type name indicates the number of windows that the crystal is adjacent to. The origin of M-type, C-type, E-type follows the naming rule in our previous research [40]. Therefore, it is expected that the 25 C-type crystals have no DOI capability.…”
Section: A Simulated Rlsw Doi Detectormentioning
confidence: 75%
See 2 more Smart Citations
“…The type name indicates the number of windows that the crystal is adjacent to. The origin of M-type, C-type, E-type follows the naming rule in our previous research [40]. Therefore, it is expected that the 25 C-type crystals have no DOI capability.…”
Section: A Simulated Rlsw Doi Detectormentioning
confidence: 75%
“…Note that no energy window was implemented because the Compton effect was not induced in the simulation. On the basis of our previous research, it was concluded that when the elongations are longer, the DOI accuracies are better [40]. To assess preliminarily the performance of DOI decoding of the three detector models, we plotted the distributions of event counts along the elongation direction of the decoded map in the blocks marked A and B in the flood maps.…”
Section: A Simulated Rlsw Doi Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…Lutetium-yttrium oxyorthosilicate (LYSO) is a scintillation crystal with efficient radiation detection characteristics, such as short decay time and high light yield [ 12 ]. LYSO has been used as an alternative to bismuth germanate (BGO) and has become the most popular scintillator in nuclear imaging systems, such as single-photon emission computed tomography (SPECT) and positron emission tomography (PET) [ 13 , 14 ]. For photon detection, photomultiplier tube (PMT) instruments are still the most popular photon sensors used in the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the DOI is of critical importance for a PET scanner with compact geometry to simultaneously achieve high and uniform spatial resolution, and high photon sensitivity ( Bailey et al 2003 , Yang et al 2016 ). Developing a practical DOI-capable PET detector with balanced performance has been studied for over two decades, including but not limited to dual-ended readout method using two detectors coupled to the both ends of crystal ( Moses and Derenzo 1994 , Miyaoka et al 1998 , Yang et al 2006 , Ling et al 2007 , Maas et al 2009 ), single-ended readout method using one detector coupled to one end of crystal ( Berg et al 2016 ), side readout method by reading signal from crystal lateral surface ( Yamaya et al 2006 , Yeom et al 2014 ), light-sharing window-based method ( Zhang et al 2019 ), monolithic scintillator detector based method ( Schaart et al 2009 ), single-ended readout method with light guide on the top surface ( Pizzichemi et al 2016 ). Among all DOI methods, dual-ended readout method has the advantages of a continuous DOI measurement and a balanced detector performance by increasing the total light output ( Shao et al 2002 , Burr et al 2004 , Yang et al 2008 , Kuang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%